Arc properties and droplet transfer characteristics in cable-type welding wire electrogas welding. (April 2018) - Chen, Yong; Fang, Chenfu; Yang, Zhidong; Wu, Mingfang; Jiang, Jiazhong; Wang, Xingxiang
Abstract: The arc properties and droplet transfer characteristics in cable-type welding wire electrogas welding were studied. A high-speed video camera and an electrical signal acquisition system were used to obtain welding arc images, the droplet transfer process and electrical signals. The results show that with an increase in welding current, the droplet transfer mode changes from globular transfer to projected transfer; the arc length decreases, the arc width increases, and the droplet size decreases. The wire extension, which ranged from 30 mm to 35 mm, has a slight effect on the droplet size, arc length and arc width. During the welding process, the arc migrates from the end of the welding wire to the necking part of the droplet. With the transition of the droplet, the arc migrates to the end of the welding wire again. As the welding current increases, the frequency of arc migration increases, and the formed droplet column becomes shorter. The rotating arc has a strong stirring effect on the molten pool, which promotes the heat transfer between the molten pool and the sidewall.